Unveiling the bee pollinators interaction with Muntingia calabura: implications for urban biodiversity conservation in tropical cityscapes - Yahya, Muhammad Syafiq; Zulkifli, Nuur Farhani; Atikah, Sharifah Nur; Sanusi, Ruzana; Azhar, Badrul; Norhisham, Ahmad Razi (Springer Nature, 2026)
Abstract: Pollinators provide crucial role in sustaining ecosystem functioning, supporting plant reproduction, and ensuring food security, however, their populations are increasingly threatened by urbanisation. Habitat loss, fragmentation, and reduced floral diversity in urban environments pose significant challenges to pollinator survival. Despite these challenges, well-managed urban green spaces, such as parks and urban grasslands, can provide critical habitats and resources to sustain diverse pollinator populations. Understanding how specific tree species, such as Muntingia calabura, influence pollinator communities, particularly bees, in tropical urban environments remains limited. This study investigates the interactions between bees and M. calabura, a common ornamental tree, in urban landscapes of Peninsular Malaysia. We quantified bee visitation patterns in relation to floral abundance, microclimatic conditions (air temperature and light intensity), season, tree distribution pattern, and urban land-use type. Our final model showed that bee visitation increased strongly with floral abundance and light intensity, while higher air temperatures were associated with reduced visitation rates. Seasonal effects were not significant. Tree distribution pattern significantly influenced visitation, with individually occurring trees receiving more visits than clustered trees. Urban land-use also had a pronounced effect, with trees located in commercial areas supporting higher bee visitation than those in residential and green areas. These findings highlight the ecological importance of M. calabura as a consistent floral resource for urban bees in tropical environments. From a management perspective, we argue that enhancing urban green spaces by prioritising the planting of pollinator-friendly tree species, such as M. calabura, can play a pivotal role in sustaining pollinator populations. Implications for insect conservation: Our study highlights the conservation value of strategically planted, pollinator-friendly urban trees, demonstrating that species such as Muntingia calabura can sustain a continuous supply of floral resources, mitigate the impacts of habitat loss, and promote ecological resilience in rapidly urbanising tropical landscapes.